The Ownership of Latrines in Southeast Sulawesi in 2020 - Tosepu, Ramadhan; ., Sumarti; Nurul Amalia, Ade; Kemal Ikhsan Rusydi, Muh.; Marwah Hamzah, Adelfima; Marwah Hamzah, Adelfima (KnE Social Sciences, 2023)
One environmental health and environmental sanitation problem in developing countries is latrine sanitation. In Southeast Sulawesi, the number of household heads with access to proper sanitation (Healthy Latrines) is 754,914 heads of families. This study aims to describe how proper sanitation ownership (Healthy Latrines) in Southeast Sulawesi Province is represented. The study uses observations with a descriptive approach. The results indicate that Kendari and Baubau had a higher percentage of healthy latrines ownership in Southeast Sulawesi in 2020, a number of 100% . Also, the Regency of North Konawe has a low percentage of healthy latrine ownership, only 53%. It is expected that the government can be more encouraging and assist in manufacturing latrines for each head of the family. Keywords: Sanitatiom, Latrine, Healthy